Reconstruction of the Nusyuz Concept of Husband Nusyuz in Mubadalah Perspective: Rekonstruksi Konsep Nusyuz Terhadap Nusyuz Suami Dalam Perspektif Mubadalah - Sarwani, Novita (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2023)
Humans as Allah's caliphs on earth have an important role in regulating the earth which is a mandate from Allah SWT. Because humans have a limited lifespan on earth, humans need regeneration so that this earth is not abandoned. This rebirth can be realized by the existence of a marriage, but in undergoing a marriage, not a few face trials in their household relationships. This can happen because one party does not carry out its obligations, so we call it nusyuz. This study aims to reconstruct the concept of nusyuz in the Qur'an. The method used in this article is a library research method. Regarding the contemporary reading of the letter An-Nisa verse 128 which explains the nusyuz of the husband. The data analysis method used is through a descriptive approach. This research the authors conclude that the concept of nusyuz does not only apply to wives but also applies to husbands, when he does not carry out his obligations as a husband.